Methods for policy research - Majchrzak, Ann. (Beverly Hills, [Calif.] ; London : SAGE, 1984)
The analysis of policies with a view to changing them is the subject of this book. Written by an expert on policy research, it shows ways of presenting alternatives to policy-makers with the emphasis on communicating the value and applicability of the research that backs up the policy options.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Policy sciences -- Research